2015
DOI: 10.1002/imhj.21512
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Psychological Well‐being and Parental Self‐efficacy in Relation to the Family's Triadic Interaction

Abstract: The aim of the study was to assess whether a parent's psychological well-being and/or self-efficacy relate to interaction within the family. This study is part of a Finnish follow-up study called Steps to the Healthy Development and Well-Being of Children (STEPS;). The study group included 120 families. Mother's and father's social anxiety and depression were assessed during pregnancy and at 18 months of the child's age using self-report questionnaires; the mother's and father's self-efficacy were assessed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
(62 reference statements)
3
13
0
Order By: Relevance
“…Maternal depression has been shown to affect the family atmosphere (Korja et al, 2015), and we similarly found marginally lower family cohesion when mothers are depressed. However, our results indicate that this affect is moderated by the nature of the father–child relationship.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Maternal depression has been shown to affect the family atmosphere (Korja et al, 2015), and we similarly found marginally lower family cohesion when mothers are depressed. However, our results indicate that this affect is moderated by the nature of the father–child relationship.…”
Section: Discussionsupporting
confidence: 77%
“…Theoretical models including psychoanalysis, attachment theory, and animal models of parental care have focused on the mother–infant bond as the cornerstone of offspring adaptation (Bowlby, 1969; Denenberg, 1964; Rosenblatt, 1967; Winnicott, 1965) and directed little attention to the family process in the context of a distinct and chronic parental psychopathology. Psychological disturbance in the parent and compromised parental well-being may cause disruptions to the family process (Dickstein et al, 1998; Korja et al, 2015). Among the most prevalent risks impacting the parent's ability to provide optimal caregiving and construct a growth-promoting family environment is maternal depression, particularly depression occurring during the child's first years of life (Goodman & Gotlib, 2002).…”
mentioning
confidence: 99%
“…Yet the coparent effects of PSE and parents' psychosocial well-being are understudied, and given that depression tends to coexist with other psychosocial problems, such as loneliness, social phobia/anxiety, and marital dissatisfaction, the accumulation of these problems may be crucial to families' overall well-being (cf. Junttila et al, 2007Junttila et al, , 2015Junttila & Vauras, 2014;Korja et al, 2015). Although the linkages between parental depression and associated PSE have been well documented (e.g., Jones & Prinz, 2005), those between the PSE of mothers and fathers and their feelings of social and emotional loneliness, social phobia, and marital dissatisfaction have been studied less.…”
mentioning
confidence: 99%
“…It is obvious that childbirth confidence is an important marker for women's coping abilities during labor and birth (Schwartz et al, 2015). Nonetheless, in a wider context, self-efficacy plays an important role in the mother-father-child triadic interaction, hence, the great influence on the family members' well-being (Korja et al, 2015). There is still a lack of scientific research about the effects of antenatal music classes on the mother's self-efficacy and the impact of postnatal music sessions on her educational self-confidence.…”
Section: Social Inclusionmentioning
confidence: 99%